Community pharmacists as antibiotic stewards: A qualitative study exploring the current status of Antibiotic Stewardship Program in Bahawalpur, Pakistan. Issue 1 (January 2020) - Atif, Muhammad; Asghar, Saima; Mushtaq, Irem; Malik, Iram
Abstract: Background: The World Health Organization released a Global Action Plan to overcome the threatening concerns of antibacterial resistance. One of the cornerstones of this plan is the Antibiotic Stewardship Program (ASP). The study aimed to assess the community pharmacists' knowledge, perceptions and current practices regarding ASP. Methods: A qualitative study was conducted in Bahawalpur, Pakistan, in which data were collected from the community pharmacists through in-depth, semi-structured interviews. The convenience sampling technique was used to recruit the study participants. Interview protocol was pilot tested and the sample size was limited by applying the saturation point criteria. All interviews were audio recorded and transcribed verbatim. The thematic analysis approach was used to analyze the data and draw conclusions based on study objectives. Results: A total of fifteen community pharmacists were interviewed. Analysis of the data yielded five themes and 16 subthemes. All of the respondents had sound knowledge about the irrational use of antibiotics; however, they were oblivious about the ASP. After explaining the term, the respondents were of the opinion that these strategies could not be implemented in the current healthcare system of the country. According to the findings of the study, prescribing and dispensing practices were not followed. Only a few patients were educated about the antibiotics they were purchasing. Conclusion: Most of the study participants were unaware of any ASP being offered in the community pharmacy settings. The study participants agreed to be the antibiotic stewards, but a number of obstacles were reported. The training of pharmacists, medication reconciliation, the implementation of the good pharmacy practice guidelines and assurance of pharmacist availability at drug retail outlets were few suggestions given by the study participants to incorporate the ASP in the community settings.